Analysis on Steady-State Electromagnetic Characteristics and Online Monitoring Method of Stator Inter-Turn Short Circuit of Turbo-Generator. Issue 2 (20th January 2017) - He, Yu-Ling; Wang, Fa-Lin; Tang, Gui-Ji; Ke, Meng-Qiang
Abstract: The intent of this paper is to find out significant united electromechanical characteristics for online monitoring of stator interturn short circuit (SISC) faults. Different from other studies, this paper pays attention to neither the stator voltage and current, nor the winding inductance variation, but focuses on the faulty electromagnetic characteristics including the exciting current, the circulating current in the parallel branches (CCPB), and the electromagnetic torque (EMT). The simulation work is modeled for a QFSN-600-2YHG type turbo-generator and the experiment is taken on a MJF-30-6 fault-simulating generator to verify the theoretical analysis. The simulation result and the experiment data accord with the theoretical analysis and show that, as SISC occurs, second harmonics will be induced in the exciting current, first and third harmonics will be induced in the CCPB, and second and fourth harmonics will be produced in the EMT. Moreover, the corresponding time-domain waves will also fluctuate intensely, while the mean value of the exciting current and the EMT will be decreased. As SISC develops, the harmonic increment, the fluctuation intensity of the time waves, and the decreased rate of the mean value will be also increased. These united characteristics can be applied to the fault diagnosis and online monitoring on SISC fault.